The atypical cyclin-like protein Spy1 overrides p53-mediated tumour suppression and promotes susceptibility to breast tumourigenesis - Fifield, Bre-Anne (Breast Cancer Res, 2019)
BACKGROUND: Breast cancer is the most common cancer to affect women and one of the leading causes of cancer-related deaths. Proper regulation of cell cycle checkpoints plays a critical role in preventing the accumulation of deleterious mutations. Perturbations in the expression or activity of mediators of cell cycle progression or checkpoint activation represent important events that may increase susceptibility to the onset of carcinogenesis. The atypical cyclin-like protein Spy1 was isolated in a screen for novel genes that could bypass the DNA damage response. Clinical data demonstrates that protein levels of Spy1 are significantly elevated in ductal and lobular carcinoma of the breast. We hypothesized that elevated Spy1 would override protective cell cycle checkpoints and support the onset of mammary tumourigenesis. METHODS: We generated a transgenic mouse model driving expression of Spy1 in the mammary epithelium. Mammary development, growth characteristics and susceptibility to tumourigenesis were studied. In vitro studies were conducted to investigate the relationship between Spy1 and p53. RESULTS: We found that in the presence of wild-type p53, Spy1 protein is held ‘in check’ via protein degradation, representing a novel endogenous mechanism to ensure protected checkpoint control. Regulation of Spy1 by p53 is at the protein level and is mediated in part by Nedd4. Mutation or abrogation of p53 is sufficient to allow for accumulation of Spy1 levels resulting in mammary hyperplasia. Sustained elevation of Spy1 results in elevated proliferation of the mammary gland and susceptibility to tumourigenesis. CONCLUSIONS: This mouse model demonstrates for the first time that degradation of the cyclin-like protein Spy1 is an essential component of p53-mediated tumour suppression. Targeting cyclin-like protein activity may therefore represent a mechanism of re-sensitizing cells to important cell cycle checkpoints in a therapeutic setting.